Oliver O'Donovan's moral theology : tensions and triumphs - Tranter, Samuel (London [England] : T&T Clark, 2020)
"This book offers the first sustained, full-length treatment of the wide-ranging work of major Anglican theologian Oliver O'Donovan. Analysing key texts written across forty years, including Resurrection and Moral Order, The Desire of the Nations, and Ethics as Theology, Samuel Tranter focuses in particular on what he argues is an area of real tension in O'Donovan's evolving vision of moral theology: the relationship between eschatology and ethics. This tension is traced as it plays out with regard to a number of important topics in O'Donovan's writing and contemporary discussion, including natural law, divine command, and human flourishing, as well as the distinctiveness or otherwise of Christian moral reasoning. Moreover, it is located alongside the broader doctrinal features of O'Donovan's project, in connection to themes such as creation, sin, and redemption, as well as to particular questions about the relationship between the cross and the resurrection. This volume also advances the reception of O'Donovan's thought by establishing and evaluating his influence upon a range of Christian ethicists and political theologians writing today (such as Luke Bretherton, Gilbert Meilaender, Jean Porter, and Brent Waters), and by engaging with critical readings of O'Donovan (such as those by Stanley Hauerwas and Gerald McKenny). Furthermore, in conversation with these scholars among an ecumenical cast of voices, Tranter offers an assessment of how O'Donovan's proposals may be appropriated and amended as a resource for theology and ethics going forward"--
Groundwork : 'the natural ethic' -- Topography : Resurrection and moral order, 'the objective reality' -- Contour : Resurrection and moral order, 'the subjective reality' -- Territory : The desire of the nations & The ways of judgment -- Remapping : ethics as theology.
Slight revision of the author's thesis (Ph.D.)--Durham Univeristy, 2018, under the title: Without elimination : with and beyond Oliver O'Donovan on eschatology and ethics.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: O'Donovan, Oliver; Christian ethics -- Anglican authors; Christian theology; Electronic books